Challenges for beyond 5G:ultra-densification of radio access network - Fumiyuki Adachi; Ryo Takahashi; Hidenori Matsuo (Tongxin xuebao)
Ultra-densification of radio access network (RAN) is a key to efficiently support the exponentially growing mobile data traffic in 5G era.Furthermore,extremely high frequency band like mmWave band was utilized to solve the bandwidth shortage problem.However,untra-dense reusing the same radio resource produced severe interference.And the mmWave link was very harsh due to frequent blockage by obstacles.Therefore a new RAN architecture needed to be introduced to realize ultra-reliable communications in such a severe radio propagation environment.An architecture of distributed MIMO based RAN was presented.Then,enhanced interference coordination (eIC) was described.Finally,the effectiveness of distributed MIMO based RAN with eIC by computer simulation was showed.